Drought Reduces Formation, but Enhances Persistence, of Mineral‐Associated Organic Matter in a Grassland Soil - Noah W. Sokol; Megan M. Foley; Steven J. Blazewicz; Nicole DiDonato; Katerina Estera‐Molina; Mary Firestone; Alex Greenlon; Bruce A. Hungate; William Kew; Ljiljana Paša‐Tolić; Eric Slessarev; Jennifer Pett‐Ridge (Global Change Biology, 2026)
Drought effects are pervasive in terrestrial ecosystems, yet there is limited understanding of how drought impacts the transformation of plant carbon (C) inputs to mineral‐associated organic matter (MAOM)—the largest and slowest‐cycling pool of soil organic carbon (SOC). In a 12‐week 13 C‐CO 2 greenhouse labeling experiment, we tracked the formation of MAOM derived from the two dominant sources of plant C input to the mineral soil—living root inputs ( 13 C‐rhizodeposits) and decaying root inputs ( 13 C‐root detritus)—under normal moisture and droughted conditions in a semiarid grassland soil. At the end of the 12‐week period, we also measured the persistence of 13 C‐MAOM formed from rhizodeposits versus root detritus via a subsequent persistence assay. Drought reduced the formation of MAOM derived from living roots by decreasing rhizodeposits, reducing microbial growth rates, and altering the composition of organic matter, lipids, and metabolites. Drought initially delayed the formation of MAOM derived from root detritus by slowing the early stages of root litter decomposition (week 4–8), but did not decrease total MAOM formation by the end of the 12‐week period. Notably, drought enhanced the persistence of MAOM derived from root detritus, but did not influence the persistence of MAOM derived from rhizodeposits. Our results provide some of the first direct evidence that drought can reduce the formation of MAOM in a grassland soil, but may enhance its persistence, based on the source of plant input from which MAOM is derived.